(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the importance of preserving our centuries-old national andreligious traditions, studying the invaluable heritage left by our ancestors, who made a significant contribution to the development of world science and culture. Italso emphasizes the importance of educating young people based on these values to become perfect individuals and create a stable spiritual environment in society.